Development of an antimicrobial wound dressing made of biocompatible polymers and metal nanoparticles for superficial treatment of diabetic foot ulcer (2020)
This project proposes the development of biodegradable and biocompatible materials with antimicrobial capacity to prevent diabetic foot ulcers (DFUs) by inhibiting methicillin-resistant Staphylococcus aureus (MRSA), which may eventually reduce healing time and incidence of infections. This pathogen has been extensively associated with skin infections and represents a problem in the treatment of these lesions, due to its resistance to commonly used antimicrobial agents. Regarding the above, the use of metal nanoparticles such as copper and silver has been proposed to inhibit the growth of resistant microorganisms, due to their broad spectrum of microbial inhibition and their effectiveness thanks to their high contact surface. First, MRSA inhibition tests with the copper and silver nanoparticles (CuONPs, AgNPs) dispersed in solution at different concentrations were carried out, in order to determine under such conditions the minimum inhibitory and bactericidal concentrations and subsequently to be able to compare it with the inhibitory concentrations obtained with the synthesized active polymeric materials. Also, tests were performed to determine the effect of the medium on the activity of the nanoparticles and their stability, as well as the effectiveness of the use of a dispersant to avoid the agglomeration of the inhibitory agents. Following this, polycaprolactone (PCL) and polyhydroxyoctanoate (PHO) films were synthetized by the solvent-casting technique, being the first commercially acquired and the second biologically synthesized by optimizing conditions for its synthesis from liquid cultures of Pseudomonas putida KT2440. Then, the nanoparticles were incorporated into polymeric solutions for synthesizing control and active films. After that, antimicrobial performance was evaluated according to the Japanese Industrial Standard JIS Z 2801 and the characterization of the materials was done, in terms of morphology, thermal properties and biocompatibility.